Mechanisms for Enhancing the Effectiveness of Individualized Home-Based Education for Children with Disabilities - Feruzakhon Usmanovna Kodirova (Euro Asian Journal Publishing, 2024)
The purpose of the research is to develop recommendations for improving the mechanisms for enhancing the effectiveness of individualized home education for children with disabilities. The study utilized various methods, including surveys, interviews, discussions, observations, pedagogical experiments, statistical data processing, graphical representation of results, and other techniques. The practical outcomes of the research are as follows:Criteria and indicators for evaluating the home education of children with disabilities have been improved.Special seminar-training programs have been developed for parents and teachers to facilitate effective home-based education for students with disabilities.The scientific significance of the research lies in improving the requirements for an integrated educational environment in individualized home education processes, based on the use of innovative educational technologies and strengthening targeted collaboration between families and educators. Additionally, it includes the creation of methodological and instructional support for the system of corrective-pedagogical work.
Keywords: effectiveness, home education, children with disabilities, families, educators